Pengembangan Kebijakan Pariwisata Religi Berbasis Moderasi Agama - Jauhariyah, Nur Anim (Proceedings of Annual Conference for Muslim Scholars, 2023)
The development of a religious tourism policy based on religious moderation in Banyuwangi Regency aims to analyze the application of religious tourism indicators as an effort to increase the quantity and quality of domestic and foreign tourist visits while maintaining religious moderation. The research method uses a qualitative approach with expert respondents from Bappeda, the Culture and Tourism Service, and the Banyuwangi Regency Tourism Awareness Group. The analysis technique uses Analytic Network Process (ANP). The research results show that the synthetic priority of developing a religious tourism policy based on religious moderation in Banyuwangi Regency on the criteria of tourist objects and attractions is 0.16 with a Kendall W concordance coefficient (rater agreement) with a high value. Visitors to religious tourism destinations who have diverse religious backgrounds and beliefs have various purposes for visiting these tourism destinations, apart from being a way to get closer to the Creator and the aim of fulfilling their life's desires. The synergy between the government, tourism managers and the community in promoting and preserving religious tourism must continue to be maintained in a sustainable manner without any conflict between beliefs.